Adverse effects and Drug Interactions Associated with Inhaled Recreational and Medical Marijuana - Maisha Kelly Freeman; Pilar Z Murphy (University of Minnesota Libraries Publishing, 2016)
Objectives: To provide an overview of the addiction potential; adverse effects (e.g., cardiovascular, immune dysfunction, respiratory system, mental health disorders); drug interactions; effects of accidental exposure; crime statistics; and pharmacist's considerations for the use of inhaled medical marijuana. Methods: A PubMed search was conducted from 1966 to March 2016 to identify articles in which the safety of inhaled medical marijuana was assessed. Key MeSH search terms included medical marijuana with a subheading for adverse effect. Only articles in adult patients were considered. In addition, medical marijuana or cannabis plus one of the following search terms were searched: drug interactions, herb-drug interactions, drug-related side effects and adverse drug reactions, substance-related disorders, addiction, and abuse. A free-text search was also conducted to identify articles not included in the MeSH term search. A bibliographic search was also conducted. Articles were included if they addressed adverse effects of medical marijuana for the treatment of a condition. Meta-analyses, randomized controlled clinical trials, and case reports were included in the review if the primary focus of the article related to the adverse effect profile of inhaled medical marijuana. Medical marijuana efficacy studies were not assessed. In the absence of this information, case reports or reports of inhaled recreational marijuana use was used. Studies were excluded if published in languages other than English. In addition, studies highlighting mechanisms of action, studies of pharmacodynamics or pharmacokinetic effects were excluded, unless these effects were due to drug-drug interactions. Prescription products containing marijuana or derivatives were excluded from evaluation. An Internet search was conducted to locate the most up-to-date information on the laws concerning medical marijuana. Key findings: A PubMed search revealed 58 articles and 28 of those studies were included in this review. Several studies were located that evaluated the safety of medical marijuana; however, much of the review focused on inhaled, recreational marijuana use due to the paucity of information on inhaled medical marijuana. Since marijuana is a Schedule1 product, few clinical studies have been conducted to determine the adverse event profile of the product. As a result, several articles that characterized recreational inhaled marijuana were included. Recreational inhaled marijuana use may be associated with an increase in cardiovascular (CV)/ cerebrovascular effects (CVA); however, conflicting information exists in the literature. Recreational marijuana use may also increase risky behaviors that increase the transmission of infectious diseases and respiratory diseases. Many of the studies were retrospective in nature; therefore, it was difficult to determine a cause and effect relationship between inhaled marijuana use and the development of adverse reactions or drug-drug interactions. Conclusions: There is a paucity of information related to the use of inhaled medical marijuana. Recreational marijuana use is associated with several adverse events including CV/CVA, respiratory, and transmission of infectious diseases. Theoretical literature indicates that medical marijuana may be associated with significant drug-drug interactions and adverse drug reactions. Legalization of medical marijuana may be associated with an increase in abuse/dependence and accidental exposures in children. Pharmacists need to be educated regarding the appropriate use of medical marijuana to avoid adverse reactions and potential drug-drug interactions between medical marijuana and other products.   Type: Original Research